Integration of Christian Theology in Character Formation of Students - Lenny Helena Sacharissa Chendralisan; Aleksky Bagoes; Daulat Marulitua Tambunan (Journal of General Education and Humanities, 2026)
This study aims to analyze the integration of Christian theology into students' character formation amid the challenges of modern education and the digital era. The main problems in education today are increasing moral degradation, low discipline, a lack of social responsibility, and the weakening of spiritual values among students. These conditions indicate that education must focus not only on academic aspects but also on character formation as a whole. This study uses a qualitative approach with a library research method. Data were obtained from various scientific journals, academic books, and the latest research results relevant to the research topic, especially publications from 2020 to 2025. Data were analyzed through content analysis, involving the review and interpretation of various sources on the integration of Christian theology and character education. The research findings show that integrating Christian theology plays a crucial role in shaping students' character by instilling Christian values such as love, honesty, discipline, responsibility, humility, and forgiveness. These values help students develop better moral behavior, spirituality, and social skills in their daily lives. The study also found that Christian Religious Education teachers play a strategic role as educators, spiritual guides, and role models for students. Furthermore, successful character formation requires collaboration between schools, families, and churches to ensure consistent internalization of values. In the digital era, Christian education must integrate theological values contextually so that students can navigate technological developments and social change without losing their moral and spiritual foundations. Therefore, integrating Christian theology into education is a relevant approach to developing a generation with strong character, moral integrity, and mature spirituality.